Peranan Teknologi Pembelajaran dalam Memecahkan Masalah Strategi Pembelajaran - Dwi Priyanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Main Contribution of educational technology in management of education and learning is open the horizon knowledge about strategic environment change. We need science and technology growth caused by activity learning and study innovation. By the way, this insufficient because technological concept of study give the formula about how carrying out teaching and learning activity in this globalization era. Then, technological application, especially ICT (Information And Communication Technology) in the education field to overcome the learning problem have a number of conditions, for example the need of expense of big enough investment and skillful energy in managing and developing education. Noteworthy that education represents the long-term investment. Therefore, investment of basic facilities of education has to be reckoned with the result of education in future